Role of Viral and Host microRNAs in Immune Regulation of Epstein-Barr Virus-Associated Diseases - Iizasa, Hisashi; Kim, Hyoji; Kartika, Andy Visi; Kanehiro, Yuichi; Yoshiyama, Hironori (Frontiers in Immunology, 2020)
Epstein-Barr viruses (EBV) belong to the Gammaherpesvirus subfamily and cause the primary acute infection “infectious mononucleosis” in adolescents. Following a primary infection in B lymphocytes or epithelial cells, EBV establishes a chronic state known as latent infection. During the latent infection, viruses escape host immune surveillance and await reactivation and switching to lytic infection to produce new virions. A small subset of viral genes and microRNAs (miRNAs) expressed during the latent infection maintain the episomal viral genome and stimulate host cell proliferation. EBV uses this strategy to propagate its progenies together with host cells. Thus, EBV infection is associated with malignancies, such as Burkitt's lymphoma, Hodgkin's lymphoma, EBV-positive diffuse large B-cell lymphoma, extranodal Natural Killer/T-cell lymphoma-nasal type, nasopharyngeal carcinoma, and EBV-associated gastric carcinoma. EBV is also responsible for severe infectious diseases, such as chronic active EBV infection. Recent advances in research has discovered not only viral latent gene products, but also non-coding RNAs, such as EBV-encoded small RNAs (EBERs) and BART microRNAs, that are abundantly expressed in latent infected cells. Host miRNAs are also upregulated upon EBV infection. This review describes the significance of BART miRNAs and host miRNAs in maintaining viral infection and enabling infected cells from evading recognition by the host immune system.